Pengembangan Daur Ulang Minyak Jelantah Menjadi Lilin Aromaterapi Berbasis Biofarmaka Di SMAN 1 Pracimantoro, Wonogiri: Pengembangan Daur Ulang Minyak Jelantah Menjadi Lilin Aromaterapi Berbasis Biofarmaka Di SMAN 1 Pracimantoro, Wonogiri - Rosiana, Diva Rauri (Journal Science Innovation and Technology (SINTECH), 2024)
Waste cooking oil is a waste that is often produced in households. Waste cooking oil is obtained from the repeated use of oil. This waste is very dangerous for the surrounding environment. This study refers to community service activities carried out at SMAN 1 Pracimantoro, Wonogiri. The target is students of SMAN 1 Pracimantoro. The purpose of the study is to re-awaken the younger generation, especially students of SMAN 1 Pracimantoro by providing an understanding of the impacts of waste cooking oil, proper processing and use of waste cooking oil, providing examples of further processing of waste cooking oil into products that have economic value, namely biopharmaceutical-based aromatherapy candles, and honing students' creativity in making unique aromatherapy candle products. The method used is through direct re-education and training. The results of the study showed an increase in understanding of waste cooking oil, can reduce pollution, and obtain products in the form of aromatherapy candles based on peppermint aroma and ginger and lemon essential oils.